Elasticity evaluation of the plantar fascia: A shear wave elastography study involving 33 early-stage plantar fasciopathy subjects - Jiang, Zhen-Zhen; Shen, Hua-Liang; Zhang, Qi; Ye, Gang; Li, Xiu-Cheng; Liu, Xia-Tian (Frontiers in Physiology, 2022)
Plantar fasciitis can be diagnosed and differentially diagnosed with imaging modalities such as ultrasound shear wave elastography (SWE). However, standard guidelines for ultrasound elastography of the plantar fascia are lacking. To determine the impact of the region of interest (ROI) on the evaluation of the plantar fascia elasticity and confirm the diagnostic value of SWE in diagnosing plantar fasciitis, the study involving 50 feet of 33 subjects (the plantar fasciitis group) and 96 asymptomatic feet of 48 healthy volunteers as well as 16 asymptomatic feet of unilateral plantar fasciitis patients (the nonpain group). Clinical information, including sex, age, height, weight, visual analogue scale (VAS) score, and American Orthopaedic Foot and Ankle Scale (AOFAS) score, was recorded. All participants underwent conventional ultrasound and SWE evaluation. The plantar fascia elastic parameters included SWE single-point and SWE multi-point. It revealed that the mean plantar fascia thickness of the plantar fasciitis group was significantly greater than that of the nonpain group. Abnormal ultrasound features were more prominent in the plantar fasciitis group than in the nonpain group. Quantitative analysis of the plantar fascia elasticity revealed that the difference between SWE single-point and SWE multipoint was significant. There was a moderate and significant correlation between the value of SWE single-point and heel pain, but no correlation between the value of SWE multipoint and heel pain. Finally, we utilized the results of SWE single-point as the best elastic parameter reflecting clinical heel pain and found that SWE single-point could provide additional value in diagnosing plantar fasciitis. Findings from the study demonstrate that the plantar fascia elastic parameter calculated with single-point ROIs set at the greatest thickness of the plantar fascia is positively correlated with fascia feel pain. SWE single-point may provide additional valuable information for assessing the severity of plantar fasciitis.